Reinterpreting Aceh-Johor relations in the 16th and 17th centuries in light of the earlier relations between the Sultanate of Pasai and the Sultanate of Malacca - Muhammad Izzuddin bin Selamat (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The fall of Malacca on August 15th 1511 to the hands of the Portuguese, created a ‎vacuum in the domination of trade and power in the Straits of Malacca during the ‎‎16th century. Three new-born powers in the region; Aceh Darussalam, Johor and the ‎Portuguese became competitors. This research was conducted to identify the causes ‎that brought to the conflict in Aceh-Johor relations during the 16th and 17thcenturies ‎in light of the earlier relationship between Pasai and Malacca. The relationship ‎between Aceh and Johor was different from that of their predecessors. They were ‎dragged into a conflict that lasted for almost 100 years. This study analyses their ‎policies and attitudes towards each other and sees how far they reflect continuity and ‎changes from the previous relations between Pasai and Malacca. This study also ‎explores the factors that led to the conflict between Aceh and Johor in the 16th and ‎‎17th centuries. Subsequent to this, the presence of the Portuguese in the region and its ‎influence on the relationship between these two kingdoms were investigated. The ‎continuity of Pasai-Malacca relations in the relationship between Aceh and Johor can ‎be seen in their partnership in military alliances, cultural activities and marriage ‎arrangements. Aceh and Johor witnessed changes in their political and economic ‎direction in the second quarter of the 16th century. Factors that contributed to the ‎changes were driven by political and economic rivalry, family commotion within the ‎royal courts and the manipulation played by the Portuguese. This study on Pasai-‎Malacca relations contribute towards a better understanding of how the Malay-‎Muslims managed to unite and treat each other respectfully. The results show how a ‎strong and united Malay-Muslim community delivered prosperity and spread the ‎message of Islam throughout the region and how the conflict stalled the progress. ‎Furthermore, the conflict in Aceh-Johor relations shed light on the role of the enemy ‎of Islam in spreading hatred and creating confusion among the Malay-Muslims. ‎